RICE- WEED ECOSYSTEM UNDER MECHANIZED SYSTEM OF RICE INTENSIFICATION (MSRI) IN NORTH COASTAL A.P. - G. PRIYANKA (The Journal of Research ANGRAU, 2016)
An experiment was conducted at the Agricultural College, Naira during Kharif, 2014 to study the correlation and regression of the grain yield of rice on certain weed and crop parameters in rice under mechanized system of rice intensification. The results revealed that the grain yield was highly negatively correlated with all the weed parameters, while the correlation was significantly positive with weed control efficiency (WCE) and weed management index (WMI). The correlation coefficient between grain yield and all crop parameters were significantly positive except with test weight, while it was significantly negative with weed index. The regression analysis indicated that there was a negative linear relationship between grain yield and dry weight of all the three groups of weeds as well as with weed density both at 50 DAP and harvest. The grain yield was reduced by 190 kg ha-1 with unit increase of weed dry weight per m-2 at 50 DAP.